Religious Response to Covid-19: A Study of Fiqh Disaster from the Perspective of Islamic-Neuroscience Education - Atmojo, Ahmad Muslih (ISTAWA, 2022)
Religion-belief in God fundamentallyÂ that has been held and believed by the majority of people. Religion is the one that governs all lines of life and procedures. During the Covid-19 pandemic, they were then asked about how religion responded to it. The fiqh disaster study is one of the answers that are quite important to consider. The importance of understanding fiqh has implications for legal development which is intended to build a goal, namely to attract maslahat and reject mafsadat. The method used in this study is library research which shintesizes the literatures related to this concern issues. The religious response is in the form of a fatwa issued by the Ulama which actually absorbs the principles of ushul fiqh (as one of the sources) which can be combined with the education-neuroscience pattern. The correlation of the religious response in this case regarding the study of fiqh principles with Islamic-neuroscience education is that jurisprudence is able to open the human mindset regarding the problems at hand, including the Covid-19 pandemic. This concept is able to change the existing worship patterns in society. From those who initially performed worship in congregation at the Mosque (for Muslims), then switched to worship which was carried out independently in their respective homes. This proves that in a situation like this, people are required to be aware of the importance of reviewing the science of religion (Islam) as a guide in carrying out life in various situations. This is as a purpose of the concern study currently when the global infacted the Covid-19 pandemic and how Islam as a religion gives solution for these problems accurately by following the quran and hadith that covered in the concept of fiqh disaster